Measuring lead time and inventory in the manufacturing of electromechanical equipment. - Moura, Greco Tusset de; Martins, Jonatas Campos; Luckow, Felipe Troglio; Sellitto, Miguel Afonso (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents an application for a calculation method of the lead-time and work-in-process inventory in xx manufacturing of electromechanical machines made after orders. Xx The concepts of lead-time and work-in-process were reviewed and the method presented. In the process, data regarding the beginning and the completion of the orders; quantities and revenues for each order, were collected. The method was applied and tested, allowing considerations about delivery time and queues in manufacturing management. Such variants can be important in a strategic scenario, in which competition also involves delivery reliability criteria. Keywords: lead-time, work-in-process, delivery time, production after orders, delivery reliability.